Reabilitação cardíaca de pacientes com doença arterial coronariana: uma estratégia de promoção da saúde - Peroni, Fabiana da Mota Almeida (2008)
This study has an explanatory feature (of the kind “study of a case”) intended to evaluate a portion of a group of people with coronary arterial disease (CAD) inserted in a Cardiac Rehabilitation Programme (CRP) and to learn how this disease has affected their quality of life. To achieve our goal we tried: to identify the social demographic data of the participants as well as the risk factors which enable us to establish precisely what this disease is; to describe the evolution of the lab exam results and the anthropometric data within three different moments along the programme. It was also observed the evolution of the life quality domain of these individuals all along the CRP. Data were collected at an Integrated Health Center in a municipality located in the Southeast of Minas Gerais during the period between August 2006 and March 2007 where they provided an ambulatorial Cardiology Service. The social demographic data, the data related to CAD risk factors, the results of the laboratory exams and the anthropometric data were all obtained either directly from the patient’s register or during home visits through a questionnaire specially worked out for this purpose. The data related to the life quality were obtained through WOQOL-100. Six participants took part in this experiment. They were five females and one male, age between 51 to 75 years old, schooling and family income were varied. The majority of them worked at home. They were all hyper tense, and five of them were diabetic. Four of them had either a mother or a father who had suffered a heart attack. None was a smoker at the time of the survey. Five of them were leading sedentary life. After a follow up period it was noted that only the HDL cholesterol showed normal rates in most of the evaluations. Although there was loss of weight the variable weight kept the body mass rate above 25. For the domínios related to the quality of life the area with minor props up was represented by the domain espiritualidade/religião/crenças personal. At as the moment, the physical domain and the quality of general life had presented reduction of prop up it, the excessively domínios ones had reached satisfactory average at the two analyzed moments. The final results bring in some thoughts about the fact that CAD is characterized as a chronic condition placing the individual and his/her family in a situation of vulnerability. The patients and their families are not always prepared to face the problems occurring from this condition. On the other hand the initiative by the local public sector to create a CRP shows the awakening of consciousness about the problem and it represents an attempt to offer a rehabilitation service that can contribute to a change in the life style and causing improvement in the quality of life of those involved in the programme. The programme also represents an attempt to promote health and its focus tries to determine not only the cause of the disease but it also tries to get to know the macro determiners of the health-disease process which can be modified through intersectors activities and a multiprofessional intervention. Key words: coronary arterial disease; risk factor; cardiac rehabilitation; promotion of health.